Evaluasi Kualitas Pengalaman Pengguna Aplikasi Duolingo Menggunakan Metode System Usability Scale (SUS) dan End User Computing Satisfaction (EUCS) - Muhammad Kahfi MS; Eliyah Acantha Manapa Sampetoding (UNIVED Press, 2025)
Background. Education has undergone a significant transformation due to digital technology, which has increased its flexibility, accessibility, and engagement. With gamifikasi strategies that increase user engagement, the Duolingo app is a highly preferred language learning resource, especially for learning English. Purpose. The System Usability Scale (SUS) and End User Computing Satisfaction (EUCS) methods will be used in this study to evaluate the usability and user satisfaction of the Duolingo program. Method. 404 respondents were obtained for this study using a quantitative approach using the Slovin formula sampling technique. Ten SUS items and five components of EUCS, content, accuracy, format, ease of use, and timeliness were included in the online survey used to collect the data. Descriptive statistics were used in the analysis to assess SUS and EUCS scores. Result. The app has a good usability level, with an average SUS score of 78.86 (grade B+). The five components, content (4.4), accuracy (4.2), format (4.5), ease of use (4.5), and timeliness (4.4), produced excellent results for EUCS. Most respondents were between the ages of 18 and 24, and they spent an average of less than 30 minutes a day. Conclusion. Particularly when it comes to usability and interface design, Duolingo offers a positive user experience and high satisfaction. Its gamifikasi strategy increases the effectiveness and engagement of English learning, especially for younger users.